Measuring crime: criminality figures and police operations in Colombia, 2017 = Midiendo el crimen : cifras de criminalidad y operatividad policial en Colombia, año 2017 - Tamayo Arboleda, Fernando León (Revista Criminalidad, 2018)
This analysis comes from a descriptive exercise of the criminal administration records obtained by the National Police of Colombia. Crimes of the country are characterized during 2017 and the main changes at subnational level are indicated, especially homicide. This crime continues the decreasing trend to one of the lowest rates in the country’s history, 25 per 100,000 population. The operational activity of the National Police is described as an outcome of the fight against crime in containment and disruption logic of crime. Similarly, the result of the National Police Code implementation is indicated through regulation and the improvement for citizen coexistence with regard to the contradictory behaviors to this issue. Finally, 38 tables are annexed that provide the reader with a national, regional and local overview of the National Police records to study crime.